2022
DOI: 10.1177/01492063221138225
|View full text |Cite
|
Sign up to set email alerts
|

High Performer Peer Effects: A Review, Synthesis, and Agenda for Future Research

Abstract: For decades, scholars and managers alike have shared a sustained interest in harnessing the talents of high-performing employees primarily due to their disproportionate contributions. An emerging research stream has begun examining the diverse effects that high performers elicit on their peers. Prior work now spans multiple organizational fields of study and utilizes a variety of high performer conceptualizations, theoretical lenses, and methodological approaches to examine the main effects of high performers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 150 publications
1
4
0
Order By: Relevance
“…On the other hand, our results also showed that managerial endorsement of coworker voice may trigger voice threat for observers, which may subsequently prompt avoidance-oriented CWB. These results parallel and build on research related how peers respond to high-performing coworkers (Campbell et al, 2017; Hendricks et al, 2023; Kim & Glomb, 2014; C. K. Lam et al, 2011).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…On the other hand, our results also showed that managerial endorsement of coworker voice may trigger voice threat for observers, which may subsequently prompt avoidance-oriented CWB. These results parallel and build on research related how peers respond to high-performing coworkers (Campbell et al, 2017; Hendricks et al, 2023; Kim & Glomb, 2014; C. K. Lam et al, 2011).…”
Section: Discussionsupporting
confidence: 72%
“…Empirical evidence provides support for this idea, demonstrating that coworkers can pose significant threats to employees when employees feel that their coworker has obtained benefits, such as more relative status (Menon et al, 2006), as would be the case when a manager endorses coworker voice. Further, research has shown that employees view high-performing peers, or those who receive favorable voice endorsement from their manager, as a direct threat to their resources (Campbell et al, 2017;Hendricks et al, 2023). Even if the coworker does not receive such benefits immediately, research has shown that anticipated future benefits for coworkers, as foreshadowed by their receipt of managerial endorsement, can trigger employees to feel threatened (Reh et al, 2018).…”
Section: Managerial Endorsement Of Coworker Voice As a Negative Stimulusmentioning
confidence: 99%
“…Thus, when they get away with unethical behavior, their peers may be more likely to follow suit. This is especially troubling in light of evidence that high performer contributions receive greater attention and can shift workgroup norms (Dalton, 1948; Hendricks, et al, 2022; Lacetera et al, 2004) and are likely to be role-modeled when they are promoted to supervisory ranks (Kim & Makadok, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In a review, Yaniv (2004, p. 75) state that 'a small number of opinions (e.g., 3-6) is typically sufficient to realize most of the accuracy gains obtainable by aggregation.' Another example is the relationship between team performance and the number of star performers, which has been extensively investigated in human resource management (Gula et al, 2021;Hendricks et al, 2023;Joo et al, 2022). The evidence suggests that hiring additional star performers yields diminishing returns across various employee teams and (Kameda et al, 2011;Lorge and Solomon, 1955), where x = number of other cooperators.…”
Section: Diminishing Returns and Self-interested Cooperationmentioning
confidence: 99%